Epidemiological and clinical features of functional dyspepsia in a region with a high incidence of esophageal cancer in China. Issue 12 (20th June 2021) - Hu, Nan; Wang, Kun; Zhang, Li; Liu, Zuo-Jing; Jin, Zhu; Cui, Rong-Li; Zhang, He-Jun; He, Zhong-Hu; Ke, Yang; Duan, Li-Ping
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Functional dyspepsia (FD) has rarely been investigated in areas with a high prevalence of esophageal squamous cell carcinoma (ESCC). This study aims to reveal the epidemiological and clinical features of FD and organic dyspepsia (OD) in such a population. Methods: A middle-aged and elderly population-based study was conducted in a region with a high incidence of ESCC. All participants completed the Gastroesophageal Reflux Disease Questionnaire and Functional Gastrointestinal Disease Rome III Diagnostic Questionnaire, and they underwent gastroscopy. After exclusion of gastroesophageal reflux disease, uninvestigated dyspepsia (UID) was divided into OD and FD for further analyses. Results: A total of 2916 participants were enrolled from July 2013 to March 2014 in China. We detected 166 UID cases with questionnaires, in which 17 patients with OD and 149 with FD were diagnosed via gastroscopy. OD cases presented as reflux esophagitis (RE), ESCC, and duodenal ulcer. Heartburn (52.94%) and reflux (29.41%) were common in OD, but no symptomatic differences were found between FD and OD. Male sex, low education level, and liquid food were the risk factors for OD, while frequent fresh vegetable consumption was a protective factor. FD included 56 (37.58%) cases of postprandial distress syndrome (PDS), 52 (34.89%) of epigastric pain syndrome (EPS), nine (6.04%) of PDS + EPS, and 32 (21.48%) of FD + functional esophageal disorders. The Helicobacter pylori infection rate in FD patients was not higher than that in the control group (34.23% vs. 42.26%, P  = 0.240). Frequent spicy food consumption was associated with PDS (odds ratio [OR]: 2.088, 95% confidence interval [CI]: 1.028–4.243), while consumption of deep well water was protective for PDS (OR: 0.431, 95% CI: 0.251–0.741). Conclusions: The prevalence of FD was 5.11% in the studied population. Gastroscopy should be prescribed for dyspepsia patients in case that ESCC and RE would be missed in UID cases diagnosed solely by the Rome III questionnaire. Trial Registration: ClinicalTrials.gov, NCT01688908; https://clinicaltrials.gov/ct2/show/record/NCT01688908 .